PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS APLIKASI PREZI PADA KOMPETENSI DASAR SULAMAN FANTASI DI KELAS XI SMK DHARMA WANITA GRESIK - Resti Wilujeng; Yulistiana Yulistiana; Inty Nahari; Peppy Mayasari (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to: (1) develop Prezi application-based learning media products on fantasy embroidery basic competencies (2) determine the feasibility of Prezi application-based learning media based on assessments from media and material experts (3) determine student responses to Prezi application-based learning media on competence basics of fantasy embroidery. The research was carried out in class XI Fashion Design at SMK Dharma Wanita Gresik. The type of research used was research and development. The development method chosen was Borg & Gall with 7 stages of development, namely data collection, planning, initial product format development, expert validation testing, revision of expert validation test results, limited field trials, revision and improvement of limited trial results. The data collection method uses a student response questionnaire, a validation test results questionnaire. Descriptive analysis techniques are used to process and analyze the results of student response questionnaires and validation questionnaires. The results of this study state that: (1) producing Prezi application-based Learning Media products on the basic competence of fantasy embroidery is good and feasible to use (2) the feasibility of Prezi application-based Learning Media products based on media experts' assessments gets a percentage of 93.75% included in the very feasible category , from material experts, an average percentage of 100% is included in the very feasible category (3) student responses to Prezi application-based learning media in the basic competence of fantasy embroidery get a percentage of 90.97% included in the very good category.